Efektivitas Pendistribusian Pupuk Bersubsidi Berdasarkan Prinsip 6 Tepat di Kabupaten Sumbawa - Wijayanti, Nila; Nurwahidah, Siti; Hartono, Yadi; Mastar, Syahdi; Pebriana, Lulu (MuJAgri: Musamus Journal of Agribusiness, 2024)
It is very crucial to evaluate the distribution of subsidized fertilizer through the application of the six rights principles (right price, quantity, type, quality, time, and place) by the government. This research aims to determine the effectiveness of the distribution of subsidized fertilizer based on the six rights principles in the Sumbawa Regency. This study is conducted in May–July 2023. The research location was determined using purposive sampling. The sample in this study was 111 people, including distributors, retailers, and farmers. The research results show that the effectiveness of subsidized fertilizer distribution based on the six correct principles varies. The right place and quality belong to very effective criteria, the right type belongs to effective criteria, and the exact amount falls into the ineffective formula. At the same time, the right price and on time belong to very ineffective criteria.